YBa2Cu3O7-z superconducting coated conductors by chemical solution deposition approach. (4th March 2017) - Zhu, X. L.; Wang, W. T.; Pu, M. H.; Cheng, C. H.; Zhao, Y.
Abstract : YBa2 Cu3 O7-δ (YBCO) superconducting coated conductors were prepared on SmBiO3 (SBO) buffered substrates by chemical solution deposition approach. In this work, SBO buffer layers with a rapid decomposition process were heat treated less than 2 h. The SBO buffer layers deposited on LaAlO3, yttria-stabilised zirconium and NiO-buffered NiW substrates possess pure SBO (l00) X-ray diffraction peaks and dense as well as smooth surface microstructures. And YBCO superconducting layers with c -axis texture and dense morphology were successfully fabricated on different SBO-buffered substrates, with superconducting transition temperature T c of 90 K and critical current density (77 K, self-field) above 1 MA cm −2 . This could offer a promising alternative to low cost and high-performance preparation of YBCO superconducting coated conductors.